Effect of Full Length Twisted Tape Inserts on Heat Transfer and Friction Factor Enhancement with Fe3O4 Magnetic Nanofluid Inside a Plain Tube: An Experimental Study - L. Syam, Sundar; Kumar, N. T. Ravi; Naik, M. T.; Sharma, K. V. (Elsevier, 2012)
Turbulent convective heat transfer and friction factor characteristics of magnetic Fe3O4 nanofluid flowing through a uniformly heated horizontal circular tube with and without twisted tape inserts are estimated experimentally. Experiments are conducted in the particle volume concentration range of 0 < u < 0.6%, twisted tape inserts of twist ratio in the range of 0 < H/D < 15and Reynolds number range of 3000 < Re < 22000. Heat transfer and friction factor enhancement of 0.6% volume concentration of Fe3O4 nanofluid in a plain tube with twisted tape insert of twist ratio H/D = 5 is 51.88% and 1.231 times compared to water flowing in a plain tube under same Reynolds number. Generalized regression equation is presented for the estimation of Nusselt number and friction factor for both water and Fe3O4 nanofluid in a plain tube and with twisted tape inserts under turbulent flow condition.